Optimal configurations for a linear vibration suppression device in a multi‐storey building. Issue 3 (26th May 2016) - Zhang, Sara Ying; Jiang, Jason Zheng; Neild, Simon
Summary: This paper investigates the use of a two‐terminal vibration suppression device in a building. The use of inerter‐spring‐damper configurations for a multi‐storey building structure is considered. The inerter has been used in Formula 1 racing cars and applications to various systems such as road vehicles have been identified. Several devices that incorporate inerter(s), as well as spring(s) and damper(s), have also been identified for vibration suppression of building structures. These include the tuned inerter damper and the tuned viscous mass damper. In this paper, a three‐storey building model with a two‐terminal absorber located at the bottom subjected to base excitation is studied. The brace stiffness is also taken into consideration. Four optimum absorber layouts, in terms of how spring, damper and inerter components should be arranged, for minimising the maximum relative displacements of the building are obtained with respect to the inerter's size and the brace stiffness. The corresponding parameter values for the optimum absorber layouts are also presented. Furthermore, a real‐life earthquake data is used to show the advantage of proposed absorber configurations. Copyright © 2016 John Wiley & Sons, Ltd.